2000
DOI: 10.1107/s0108270199012160
|View full text |Cite
|
Sign up to set email alerts
|

(−)-Sparteine copper(II) diacetate

Abstract: The chiral nitrogen‐chelating alkaloid (−)‐sparteine acts as a bidentate ligand, reacting with copper(II) acetate in ethanol to form the title complex, [Cu(CH3COO)2(C15H26N2)], with the two acetate groups occupying the remaining coordination sites in a monodentate fashion to produce a distorted four‐coordinate tetrahedral structure. The dihedral angle between the N—Cu—N and O—Cu—O planes is 45.8 (3)°.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Structural information on copper (À)-sparteine complexes appears at present to be limited to dichloro{(À)-sparteine}copper(II) 3 and {(À)-sparteine}copper(II) diacetate. 4 Owing to our ongoing interest in complexes between copper(I) and hard-donor ligands 5 and, moreover, in the use of various metal complexes containing chiral ligands for organic synthetic applications, 6,7 we embarked on an investigation of those complexes formed in a direct reaction between copper(I) chloride and (À)-sparteine.…”
Section: Introductionmentioning
confidence: 99%
“…Structural information on copper (À)-sparteine complexes appears at present to be limited to dichloro{(À)-sparteine}copper(II) 3 and {(À)-sparteine}copper(II) diacetate. 4 Owing to our ongoing interest in complexes between copper(I) and hard-donor ligands 5 and, moreover, in the use of various metal complexes containing chiral ligands for organic synthetic applications, 6,7 we embarked on an investigation of those complexes formed in a direct reaction between copper(I) chloride and (À)-sparteine.…”
Section: Introductionmentioning
confidence: 99%
“…the formation of complexes with transition metal(II) leads to a conversion of the nitrogen atom configuration in the sparteine ligand: as a consequence, all four alkaloid rings adopt the chair configuration and the configuration at the A/B and c/D ring junctions are trans and cis, respectively. [19][20][21][22][23][24]26,27 this conformation differs from that of the free (-)-sparteine ligand. 32,33 on the other hand, it has been reported that (-)-a-isosparteine remains structurally unchanged upon complexation 25,28 (figure 2).…”
mentioning
confidence: 99%
“…considerable effort has been devoted to the study of these compounds by infrared and nuclear magnetic resonance spectroscopy, as well as by X-ray methods. [18][19][20][21]23,24,[26][27][28][41][42][43][44][45] However, the EI and fAB fragmentations of these compounds have not been reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 The formation of complexes leads to a conversion of the nitrogen atom configuration in the sparteine ligand; as a consequence, all four alkaloid rings adopt the chair conformation, and the configurations at the A/B and C/D ring junctions are trans and cis, respectively. 15,[22][23][24] This conformation differs from that of the free (-)-sparteine ligand, in which the C ring takes the boat form, and the configuration at the C/D ring junction is trans.…”
mentioning
confidence: 99%